2015
DOI: 10.1002/sdtp.10194
|View full text |Cite
|
Sign up to set email alerts
|

50.2: Invited Paper: Stroboscopic Effect of LED Lighting

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The mean threshold, expressed as modulation depth, is 0.4 at the lowest illumination level of 5 lux; it decreases to 0.18 at 50 lux, and then increases again to 0.27 at 500 lux. Similar perception experiments have been conducted in a research lab in China [11], and the results were found to be consistent across the labs, indicating that the SVM can be representing a "standard observer".…”
Section: Figuresupporting
confidence: 70%
“…The mean threshold, expressed as modulation depth, is 0.4 at the lowest illumination level of 5 lux; it decreases to 0.18 at 50 lux, and then increases again to 0.27 at 500 lux. Similar perception experiments have been conducted in a research lab in China [11], and the results were found to be consistent across the labs, indicating that the SVM can be representing a "standard observer".…”
Section: Figuresupporting
confidence: 70%
“…One possible concern with our implementation refers to the health issues possibly associated with prolonged exposure to stroboscopic light sources. Indeed, the long‐term effects of exposure to stroboscopic light remain unclear, even at high frequencies . However, we point out that our system is primarily to be used in tandem or integrated with existing imaging devices, such as clinical endoscopy, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…A similar disk has been used many times in the previous researches. 23 The speed of 4 m/s is comparable to an upper limit of the speed of hand movements' in a general lighting application, such as an office. Then subjects' feelings are measured by the same visual perception scale.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects can clearly perceive the flicker and the dispersed spatial motion in high-risk zone conditions, which is consistent with the results of a previous paper. 23 It is clear that the stroboscopic effect has an influence on the perception of spatial movement, which will indirectly impact workers' performance, and may even produce potential safety hazards. Besides, workers affected by the office lighting have a poor assessment on the difficulty of the task according to the analysis of work cognition, which supports the conclusion of Nilsson Tengelin et al 28 Generally speaking, the stroboscopic effect causes bad spatial motion evaluations (discrete spatial motion and severe flicker) and work cognition according to the third hypothesis.…”
Section: Figure 14mentioning
confidence: 99%